ASSESSMENT OF QUALITY RISK FACTORS DURING THE CONSTRUCTION PHASE OF THE BICONSI TOWER PROJECT - Phan, Phuong Thanh; Nguyen, Phong Thanh; Nguyen, Quan Khac (Journal of process management and new technologies, 2022)
Project performance is assessed using various criteria. Quality is one of the typical triangle criteria used to assess the performance of any office building project. However, office projects in Vietnam have faced numerous quality risks, particularly during their construction periods. This can cause the building projects to be delayed and over budget. As a result, identifying quality risk factors throughout the construction phase of office projects is essential. Therefore, this paper applies the analytical hierarchy process to prioritize critical risk factors affecting project quality during the construction phase of the Biconsi Tower project in Vietnam. The research results show that the five top risk factors affecting the quality of the Biconsi Tower project from most to least impact are as follows: (1) inspection and approval work are not in accordance with regulations and procedures, (2) lack of coordination between project stakeholders, (3) poor quality design documents and drawings, (4) poor construction methods, and (5) poor quality input materials.